An update on equine post‐operative ileus: Definitions, pathophysiology and management. (29th January 2018) - Lisowski, Z. M.; Pirie, R. S.; Blikslager, A. T.; Lefebvre, D.; Hume, D. A.; Hudson, N. P. H.
Summary: Post‐operative ileus (POI) is a serious condition which any horse undergoing abdominal surgery is at risk of developing, leading to increased hospitalisation time and resulting costs. Advances in the understanding of the development of equine POI are mainly based on human and rodent literature, where manipulation‐induced inflammation has been identified as a trigger, with activation of resident muscularis externa macrophages playing a crucial role in the pathophysiology. Despite many pharmacological trials in all species, there is no single completely successful treatment for POI, highlighting that the condition is multifactorial in cause and requires a multimodal approach to minimise its incidence.